Impact of primary health care on mortality from heart and cerebrovascular diseases in Brazil: a nationwide analysis of longitudinal data - Rasella, Davide (2014)
Barreto, Mauricio Lima. Fundação Oswaldo Cruz. Instituto Gonçalo Moniz. “Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta à informação no documento”.